Treating breathlessness via the brain: changes in brain activity over a course of pulmonary rehabilitation - Herigstad, M; Faull, O; Hayen, A; Evans, E; Hardinge, FM; Wiech, K; Pattinson, K (European Respiratory Society, 2017)
Background. Breathlessness in chronic obstructive pulmonary disease (COPD) is often discordant with airway pathophysiology ("over-perception"). Pulmonary rehabilitation profoundly affects breathlessness, without influencing lung function. Learned associations influence brain mechanisms of sensory perception. We hypothesised that improvements in breathlessness with pulmonary rehabilitation may be explained by changing neural representations of learned associations. Methods. In 31 patients with COPD, we tested how pulmonary rehabilitation altered the relationship between brain activity during a breathlessness-related word-cue task (using functional magnetic resonance imaging), and clinical and psychological measures of breathlessness. Results. Changes in ratings of breathlessness word-cues positively correlated with changes in activity in the insula and anterior cingulate cortex. Changes in ratings of breathlessness-anxiety negatively correlated with activations in attention regulation and motor networks. Baseline activity in the insula, ACC and prefrontal cortex correlated with improvements in breathlessness and breathlessness anxiety. Conclusions. Pulmonary rehabilitation is associated with altered neural responses related to learned breathlessness associations, which can ultimately influence breathlessness perception. Word-cue related brain activity at baseline was correlated with changes in word-cue ratings over the course of pulmonary rehabilitation. These findings highlight the importance of targeting learned associations within treatments for COPD, demonstrating how neuroimaging may contribute to patient stratification and more successful personalised therapy.